A Literature Review Revisiting Phenytoin-Induced Sinus Arrest. (July 2016) - Parsai, Shireen; Hariri, Imad; Taleb, Mohammad; Yoon, Youngsook
Abstract : Classically, phenytoin (PTN) infusion for the treatment of status epilepticus has been proven to be associated with cardiovascular toxicity, including dysrhythmias, hypotension, and cardiovascular collapse. Subsequently, fosphenytoin (FOS) was introduced on the market in 1997 with claims of having less cardiac toxicity. However, since then, many accounts of cardiac events have been reported undermining these claims. FOS gained popularity due to its water solubility, which allows 3 times faster infusion in comparison with PTN with less venous irritation and local toxicity. FOS is the phosphate ester prodrug of PTN and is rapidly converted to PTN independent of the dose and rate of administration. Intravenous FOS and PTN are bioequivalent. Adverse cardiac effects of both intravenous FOS and PTN have been correlated to the rate of infusion, concentration of the agent, known risk factors, or pre-existing hypersensitivity, and most cases have been identified after infusing a loading dose of these medications. This case report is unique, in that, the patient developed sinus arrest while concurrently receiving oral PTN and intravenous FOS. Clinicians should be more cognizant of the association of FOS and PTN with adverse cardiac events. Baseline electrocardiogram should be obtained on all patients prescribed FOS or PTN to identify underlying cardiac problems that may place the patient in a higher risk category. Telemetry should be performed on all patients receiving PTN in an inpatient setting.